2021
DOI: 10.1155/2021/9995869
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of DLBCL Progression by the E3 Ligase Trim35 Is Mediated by CLOCK Degradation and NK Cell Infiltration

Abstract: The majority of diffuse large B-cell lymphoma (DLBCL) patients develop relapsed or refractory disease after standard ruxolitinib, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) chemotherapy, which is partly related to a dysregulated tumor immune microenvironment. However, how the infiltration of immune cells is appropriately regulated is poorly understood. Herein, we show that the E3 ubiquitin ligase Trim35 is expressed at low levels in human DLBCL tissues. We also show that overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Therefore, inhibition of MDM2 E3 ligase increased anti-PD-1/PD-L1 therapeutic efficacy via regulation of immune and stromal microenvironment in p53 wild-type cancer patients. Trim35 E3 ligase influenced the TIME and reduced the DLBCL progression via targeting a regulator of circadian rhythmicity CLOCK for degradation and modulating NK cell infiltration ( 117 ). Galectin-9 augmented an immunosuppression in TME via accelerating TRIM29-mediated degradation of STING in human cancers ( 118 ).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Therefore, inhibition of MDM2 E3 ligase increased anti-PD-1/PD-L1 therapeutic efficacy via regulation of immune and stromal microenvironment in p53 wild-type cancer patients. Trim35 E3 ligase influenced the TIME and reduced the DLBCL progression via targeting a regulator of circadian rhythmicity CLOCK for degradation and modulating NK cell infiltration ( 117 ). Galectin-9 augmented an immunosuppression in TME via accelerating TRIM29-mediated degradation of STING in human cancers ( 118 ).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…E3 ubiquitin ligases have been reported to function in DLBCL, such as Trim35 (Tan et al, 2021), Smurf2 (Ramkumar et al, 2013), cIAP1 and cIAP2 (Yang et al, 2016), which participate in diversified physiological processes in cells by mediating protein ubiquitination. As a founding member of the ubiquitin ligase family, NEDD4 takes on a crucial function in the regulation of plentiful membrane receptors, components of the endocytic machinery, and the tumor suppressor PTEN (Boase & Kumar, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This study verified NEDD4 was reduced in DLBCL patient tissues and cells, and elevation of NEDD4 could restrain DLBCL tumor proliferation and growth in vitro and in vivo, which was linked with FOXA1 ubiquitination and Wnt/β-Catenin pathway. These results convey NEDD4 may be a novel latent marker for the diagnosis and cure of DLBCL.E3 ubiquitin ligases have been reported to function in DLBCL, such as Trim35(Tan et al, 2021), Smurf2(Ramkumar et al, 2013), cIAP1 and cIAP2(Yang et al, 2016), which participate in diversified physiological processes in cells by mediating protein ubiquitination.F I G U R E 7 Elevation of NEDD4 restrains DLBCL's growth in vivo. (a) Growth curve of FARAGE cells injected subcutaneously in mice; (b) Tumor pictures of mice; (c) Tumor weight of mice with transplanted tumors.…”
mentioning
confidence: 94%
“…Inhibition of TRIM35 expression in non-small cell lung cancer cell lines promoted cell proliferation, migration and invasion ( 39 ). Another study reported that E3 ubiquitin ligase TRIM35 is expressed at a low level in diffuse large B-cell lymphoma ( 40 ). Overexpression of TRIM35 inhibited the proliferation of diffuse large B-cell lymphoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of TRIM35 inhibited the proliferation of diffuse large B-cell lymphoma cells. A mechanistic study demonstrated that TRIM35 mediates ubiquitination and degradation of 'clock', a key regulator of the circadian rhythm ( 40 ). The present study further indicated that the expression of TRIM35 was lower in breast cancer and its low expression was associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%